2007
DOI: 10.1007/s11906-007-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional renin receptors in renal mesangial cells

Abstract: Activation of the renin-angiotensin system (RAS) and generation of angiotensin II (Ang II) play a crucial role in fibrotic renal disease beyond this system's hemodynamic actions. Ang II blockade was a great therapeutic breakthrough for renal and cardiovascular diseases; however, this slows, but does not stop, disease progression. These limitations leave other molecules unopposed to sustain disease progression. One is renin, which is markedly elevated by Ang II blockade. Recently, a new renin receptor was clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…When mice expressing human AGT were crossed with a line expressing a human mutant prorenin that was noncleavable, the elevation of ANG I content in the pituitary gland continued, suggesting that prorenin activation within the pituitary gland is not due to proteolytic cleavage of prorenin (22). Consistent with the data presented here using VSMCs, the nonproteolytic activation of prorenin in vivo in the double-transgenic mouse is likely mediated by the (p)RR, since (p)RR is abundant in the pituitary gland (11).…”
Section: Discussionsupporting
confidence: 82%
“…When mice expressing human AGT were crossed with a line expressing a human mutant prorenin that was noncleavable, the elevation of ANG I content in the pituitary gland continued, suggesting that prorenin activation within the pituitary gland is not due to proteolytic cleavage of prorenin (22). Consistent with the data presented here using VSMCs, the nonproteolytic activation of prorenin in vivo in the double-transgenic mouse is likely mediated by the (p)RR, since (p)RR is abundant in the pituitary gland (11).…”
Section: Discussionsupporting
confidence: 82%
“…[40][41][42] It has been shown that (pro)renin binding to PRR provokes a rapid activation of mitogen-activated protein kinase and promotes matrix gene expression in an angiotensin II-independent fashion. 41,43,44 Furthermore, PRR is also an integral component of the Wnt receptor complex, and it augments Wnt signaling in a renin-independent manner. 45,46 Therefore, it is conceivable that some of the pathogenic effects of RAS components are independent of angiotensin II, which could account for the limited efficacy of current therapy through ACEIs and ARBs.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 TGFβ1 is also a downstream target of AngII 31 and can be up-regulated by renin in mesangial cells through the pro(renin) receptor independently of AngII. [32][33][34] Treatments with aliskiren or valsartan significantly reduced the gene expression of TGFβ, CTGF and PAI-1 therefore preventing kidney injury in diabetes. In addition, at the doses used in this study aliskiren demonstrated a better effect than valsartan in preventing increase of proinflammatory cytokines TNF-α, MCP-1 and IL1-1β in the kidneys of the diabetic mice.…”
Section: Discussionmentioning
confidence: 99%